Biofilm Formation by Pseudomonas aeruginosa in a Novel Septic Arthritis Model - Li, Dingbin; Zhang, Li; Liang, Jinhua; Deng, Wusheng; Wei, Qingjun; Wang, Ke (Frontiers in Cellular and Infection Microbiology, 2021)
Background Bacterial biofilms generally contribute to chronic infections and complicate effective treatment outcomes. To date, there have been no reports describing biofilm formation in animal models of septic arthritis caused by Pseudomonas aeruginosa (P. aeruginosa). P. aeruginosa is an opportunistic pathogenic bacterium which can lead to septic arthritis. The purpose of this study was to establish a rabbit model of septic arthritis caused by P. aeruginosa to determine whether it leads to biofilm formation in the knee joint cavity. In addition, we explored the role of cyclic di-GMP (c-di-GMP) concentrations in biofilm formation in rabbit models. Methods Twenty rabbits were randomly assigned to five groups: PAO1 (n = 4), PAO1ΔwspF (n = 4), PAO1/plac-yhjH (n = 4) infection group, Luria–Bertani (LB) broth (n = 4), and magnesium tetrasilicate (talc) (n = 4) control groups. Inoculation in the rabbit knee of P. aeruginosa or with the same volume of sterile LB or talc in suspension (control group) was used to induce septic arthritis in the animal model. In the infection groups, septic arthritis was caused by PAO1, PAO1ΔwspF, and PAO1/plac-yhjH strains, respectively. Rabbits were euthanized after 7 days, and pathological examination of synovial membrane was performed. The biofilms on the surface of the synovial membrane were observed by scanning electron microscopy, while the biofilms’ fiber deposition was discriminated using peptide nucleic acid-fluorescence in situ hybridization (PNA-FISH). Results A rabbit model for knee septic arthritis induced by P. aeruginosa was successfully established. Scanning electron microscopy revealed that PAO1 strains were surrounded in a self-produced extracellular matrix on the surface of synovial membrane and showed biofilm structures. The biofilms in the fibrous deposition were also observed by PNA-FISH. The PNA-FISH assay revealed that the red fluorescence size in the PAO1ΔwspF group was greater than in PAO1 and PAO1/plac-yhjH groups. Conclusions This is the first study to provide evidence that P. aeruginosa forms biofilms in a rabbit model for septic knee arthritis. The rabbit model can be used to investigate new approaches to treatment of biofilms in septic arthritis. Furthermore, c-di-GMP is a key signaling molecule which impacts on biofilm formation in rabbit models of knee septic arthritis.